Pelaksanaan Penerbitan Sertifikat Pengganti di Kantor Pertanahan Wilayah Kabupaten Kotawaringin Barat - Alifa Putri Rahmadhani (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Protecting the rights and interests of the people has an important role for the government. To prevent the increasing number and development of land conflicts in the community, it is very necessary to make definite resolution efforts, for example to meet the needs of the community which is usually used for residence, livelihoods and daily needs, it is necessary to provide legal protection for land rights, and especially property rights to land which are owned by many people. From the description above, land ownership certificates are very important to maintain, but up to now there are still requests for replacement certificates due to loss and damage, so the author is interested in studying in more depth the responsibility of the West Kotawaringin Regency BPN for issuing replacement certificates. The author uses empirical legal research. The data analysis technique was carried out descriptively, qualitatively, namely by providing presentations and explaining in detail and in depth and for data collection by searching for data and information in relevant locations related to the research topic using interviews, literature studies and the internet.